Green approach to photoluminescent carbon dots for imaging of gram-negative bacteria Escherichia coli. (18th April 2017) - Das, Poushali; Bose, Madhuparna; Ganguly, Sayan; Mondal, Subhadip; Das, Amit Kumar; Banerjee, Susanta; Das, Narayan Chandra
Abstract: Fluorescent carbon dots, zero-dimensional nanomaterials with surface ligands, have been studied extensively over the past few years in biolabelling or fluorescence-based live cell assays. In the past, synthetic organic dyes have been used as cell tracking materials, but they have severe limitations; fluorescent carbon dots may pave the way to biolabelling and cell imaging. In this work, green fluorescent carbon dots have been synthesized from a green source, gram, without any sort of covalent or ionic modifications. These gram-derived carbon dots are unique with respect to synthetic commercial cell-tracking dyes as they are non-toxic, cell internalization occurs quickly, and they have excellent bioconjugation with bacterial cells. Our aim is to establish these carbon dots in a biolabelling assay with its other physicochemical features like the tunable luminescence property, high degree of water solubility and low toxicity, towards various environments (wide range of pH, high ionic strength). Our study introduces a new perspective on the commercialization of carbon dots as a potential alternative to synthetic organic dyes for fluorescence-based cell-labelling assays.